Etnografi Virtual Grup Facebook Meme Dakwah Islam - Riski Septiawan (INTELEKSIA - Jurnal Pengembangan Ilmu Dakwah, 2022)
Along with the development of internet, smartphone, and social media technology, human behavior also develops. With this technology, humans form virtually new societies. They interact and form collective relationships without the need to meet and get to know. The Islamic Da'wah Meme group on Facebook is no exception, a virtual group that is a forum for internet users to express their creativity and passion for virtual da'wah through memes. The purpose of this research is to examine the interaction of virtual communities in the Islamic Da'wah Meme Group on Facebook. This research was conducted qualitatively with virtual ethnographic method. Data obtained from group document archives, group administrator statements, and observation records during the group activity. The analysis was performed using the Miles and Hubberman model. The results showed that memes were a virtual culture that emerged with the internet. It was realized that meme could be used as a means of preaching because it could be filled with goodness and Islamic content. As a means of preaching via the internet, memes have the power to provide information, invite, insinuate, and so on with entertaining packaging. This group was born because of the need to preach through memes. With this group, everyone can learn to make da'wah memes, spread da'wah memes, to just be connoisseurs and gain insight.